2015
DOI: 10.5152/akd.2014.5578
|View full text |Cite
|
Sign up to set email alerts
|

Coronary slow flow: Benign or ominous?

Abstract: Objective:Coronary slow flow phenomenon has been arbitrarily defined as delayed coronary blood flow in the absence of obstructive coronary artery disease. The present study sought to investigate the clinical features, natural history, and outcomes of affected patients.Methods:In this prospective cross-sectional study, 217 consecutive patients who had undergone coronary angiography and showed features of coronary slow flow phenomenon were evaluated for demographic and coronary risk factor profile, as well as cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
4
17
0
1
Order By: Relevance
“…Little is known about the prognosis of true primary CSFP, because the most published literature has included patients with known heart failure, near-normal coronary arteries (<40% stenosis), and other unexplained diseases [12, 13], and as a result, their outcome was not substantially the same as that observed in this study. In this study, we have tried to exclude patients with a possible secondary form of CSFP and other disease states as has been said before by sticking to very strict inclusion and exclusion criteria.…”
Section: Discussionmentioning
confidence: 67%
“…Little is known about the prognosis of true primary CSFP, because the most published literature has included patients with known heart failure, near-normal coronary arteries (<40% stenosis), and other unexplained diseases [12, 13], and as a result, their outcome was not substantially the same as that observed in this study. In this study, we have tried to exclude patients with a possible secondary form of CSFP and other disease states as has been said before by sticking to very strict inclusion and exclusion criteria.…”
Section: Discussionmentioning
confidence: 67%
“…A função microvascular coronária deteriorada no FCL demonstrou uma relação com o aumento do risco de eventos cardiovasculares. [25][26][27] Além disso, foi relatado que, nos pacientes com disfunção microvascular, o prognóstico é semelhante àquele observado na doença arterial coronariana obstrutiva, e que essa disfunção não é tão benigna quanto se pensava. [28][29][30] As manifestações clínicas dessa patologia também estão associadas a achados significativos.…”
Section: Discussionunclassified
“…These are traditional CAD risk factors which supports the theory of subclinical atherosclerosis role in CSF pathogenesis (involving increased sympathetic activity, inflammatory response, endothelial dysfunction, abnormal platelet activation and release of its products). [4] However, previous studies examining this association showed conflicting results: male gender and high TG levels were significant independent predictors of CSF in some studies,[18,19] while others found no relationship between gender and CSF. [20] As for high TG, the present study is consistent with previous one by Dai YX et al, who reported that patients with high levels of TG (in addition to high fasting blood glucose and low levels of HDL) were more likely to have CSF.…”
Section: Discussionmentioning
confidence: 99%